Roles of the Snf1-Activating Kinases during Nitrogen Limitation and Pseudohyphal Differentiation in Saccharomyces cerevisiae - Orlova, Marianna (American Society for Microbiology (ASM), 2010)
In Saccharomyces cerevisiae, Snf1 protein kinase is important for growth on carbon sources that are less preferred than glucose. When glucose becomes limiting, Snf1 undergoes catalytic activation, which requires phosphorylation of its T-loop threonine (Thr210). Thr210 phosphorylation can be performed by any of three Snf1-activating kinases: Sak1, Tos3, and Elm1. These kinases are redundant in that all three must be eliminated to confer snf1Δ-like growth defects on nonpreferred carbon sources. We previously showed that in addition to glucose signaling, Snf1 also participates in nitrogen signaling and is required for diploid pseudohyphal differentiation, a filamentous-growth response to nitrogen limitation. Here, we addressed the roles of the Snf1-activating kinases in this process. Loss of Sak1 caused a defect in pseudohyphal differentiation, whereas Tos3 and Elm1 were dispensable. Sak1 was also required for increased Thr210 phosphorylation of Snf1 under nitrogen-limiting conditions. Expression of a catalytically hyperactive version of Snf1 restored pseudohyphal differentiation in the sak1Δ/sak1Δ mutant. Thus, while the Snf1-activating kinases exhibit redundancy for growth on nonpreferred carbon sources, the loss of Sak1 alone produced a significant defect in a nitrogen-regulated phenotype, and this defect resulted from deficient Snf1 activation rather than from disruption of another pathway. Our results suggest that Sak1 is involved in nitrogen signaling upstream of Snf1.